Teori Perkembangan Afektif: Teori Perkembangan Afektif - Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2022)
Actually, the learning process does not only focus on elements of student intelligence or cognitive aspects, but also attitudes, behavior, and emotions or what is commonly known as the affective aspect. The affective domain is related to attitudes and values, affective is everything related to attitudes, character, behavior, interests, emotions, and values ​​that exist within each individual. According to some experts, affective is closely related to cognitive. The higher a person's level of cognitive power, the easier it is to predict changes in behavior. If viewed from learning in class, learning outcomes can have an impact on changes in student behavior. When teaching, you must be familiar with the various characters and behavior of students in class. The number of such characters will certainly be a challenge for teachers, who strive to make all students achieve maximum results. Even so, a professional teacher must still try to pay attention to students in the class so that they can grow and develop into better individuals. Affective is one of the three domains that are targeted in the learning process. Affective has been a part of learning in schools for decades. It appears in many different forms such as humanist education, moral development, self-actualization, values ​​education, etc. Affective also appears as a response to various social needs such as the widespread use of drugs and promiscuity. Affective learning is related to the experiences of students at school and generally describes programs related to personal social development.